The Effect of Customer Trust and Product Diversity on Shopee Users Repurchase Intention with Customer Satisfaction as a Moderating Variable - Isma Maisarah; Ari Soeti Yani (IJHCM (International Journal of Human Capital Management), 2022)
This study aims to test and analyze the effect of discounts and sales promotion on repurchase intention with customer satisfaction as a moderating variable. The population in this study used a sample of 344 respondents who were users of the Shopee application aged 18-28 years. The data collection technique uses simple random sampling by spreading research questionnaires in the form of google forms through social media. The data processing method in this study is to use smartPLS with the aim of testing hypotheses. The results of this study show that customer trust has a positive and significant effect on repurchase intention, product diversity has a positive and significant effect on repurchase intention, customer satisfaction has a positive and significant effect on repurchase intention, customer satisfaction is significant and can moderate the effect of customer trust on repurchase intention, customer satisfaction has a significant effect on repurchase intention and can moderate the effect of product diversity on repurchase intention. This research recommends to shopee if you want to increase consumer repurchase interest, then it is possible to be able to further increase the sense of customer trust, because some respondents to this study stated that shopee has not fully provided quality products so that the products purchased are not in accordance with expectations, but this can be minimized by checking and ensuring that each product is worthy of being traded. Shopee is also expected to maintain the level of product availability, so that consumers can feel satisfied and return to shopping.Customer Trust, Product Diversity, Repurchase Intention, Customer Satisfaction